Faktor-faktor Yang Mempengaruhi Kinerja Karyawan CV. Dijawa Abadi Melalui Kepuasan Kerja Sebagai Variabel Intervening - Yunita Ayu Maulidiyah; Ika Indriasari; Bayu Kurniawan (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This research was backgrounded by the efficiency of CV's production division. Dijawa Abadi is low compared to other divisions that are already included in the efficient division. Employee performance is the result of a process that refers to and is measured over a period of time based on predetermined terms and agreements. The purpose of this study is to determine the Effect of Motivation, Work Environment and Compensation on Employee Performance through Job Satisfaction as an Intervening Variable in CV. Dijawa Abadi, by taking a sample of respondents through alumni as many as 152 employees of the CV production department Dijawa Abadi. The number of samples was taken using sampling techniques using nonprobability sampling methods. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS version 3 software. The results showed that Motivation, Work Environment and Compensation affect Employee Performance through Job Satisfaction.